Peran Pendidikan dan Diklat terhadap Promosi Jabatan Pegawai Negeri Sipil - Achmad Irvan; Marno Nugroho (Yayasan Jompa Research and Development, 2026)
This study uses a quantitative explanatory approach and Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to analyze the role of education and training in competence and job promotion among civil servants in the Government of Kotawaringin Barat Regency. The study also examines competence as an intervening variable in the relationship between education, training, and job promotion. The population consisted of 2,154 active civil servants, and 146 respondents were selected using proportional stratified random sampling. Data were collected through a structured questionnaire. The findings indicate that education and training significantly improve employee competence. Education and training also contribute directly to job promotion, while competence shows the strongest effect on job promotion among all direct relationships in the model. In addition, competence significantly mediates the relationship between education and job promotion, as well as the relationship between training and job promotion. The coefficient of determination indicates that education and training explain 46.2% of the variance in competence, while education, training, and competence explain 54.8% of the variance in job promotion. These findings imply that the implementation of a merit-based promotion system in local government should not rely solely on formal education and participation in training, but also on measurable competence development aligned with job requirements.